Catalysis of oxygen reduction reaction for H2O2 electrogeneration: The impact of different conductive carbon matrices and their physicochemical properties - Marques Cordeiro-Junior, Paulo Jorge; Kronka, Matheus Schiavon [UNESP]; Goulart, Lorena Athie; Verissimo, Nathalia Carolina; Mascaro, Lucia Helena; Santos, Mauro Coelho dos; Bertazzoli, Rodnei; Vasconcelos Lanza, Marcos Roberto de [UNESP] (Elsevier B.V., 2020)
Carbon-based catalysts are widely used in oxygen reduction reactions (ORR) via 2e- H2O2 electrogeneration. The direct comparability of the structural proprieties of different carbon matrices applied on ORR, however, has never been tested. Here, we evaluate how the electrochemical and structural properties of different carbon-based materials, including carbon Printex XE2B (PXE2BC), Printex L6 (PL6C), carbon derived from lignin (LIGC), graphite (GRA) and glassy carbon (GC), affect on ORR. All the materials were characterized by Raman spectroscopy, X-ray photoelectron spectrometry (XPS), elementary analysis, field emission gun scanning electron microscopy, surface area measurements and electrochemical assays for the evaluation of ORR. Notably, the morphology, the size of the particles and the types of functional groups present in the structure of carbon materials were keys in the efficiency of ORR. The carbon materials PL6C and PXE2BC with high surface area and oxygenated functional groups in their structure displaced the ORR potential, facilitating the reaction. Carbon materials with less surface area, such as GRA, LIGC and GC, and whose main functional groups in their structures were non-oxygenated or nitrogenated, were less active in ORR. The displacement of the potential and the efficiency of H2O2 generation were directly dependent on the electrochemical and structural characteristics of the materials used as catalysts. These results are particularly relevant regarding a proper choice of carbon catalyst can increase the efficiency of ORR. (C) 2020 Elsevier Inc. All rights reserved.
Keywords: Carbon-based materials; Oxygen reduction reaction; Hydrogen peroxide electrosynthesis; Structural and electrochemical characterization